A influência do reflorestamento da mata ciliar sobre a estrutura da comunidade de macroinvertebrados bentônicos em rios de baixa ordem - Franke, Marcela Cristiane (2012)
Riparian forests protect water flows and allow the allocation of food and habitat for macroinvertebrates. With the impact of the absence of riparian forests, the benthic macroinvertebrate communities are changed and even after these reforestation, this community takes time to restructure. Thus, in this study we estimated the time needed reforestation of riparian vegetation for the community of benthic macroinvertebrates in streams of low order, similar to the present structure of environments not changed. Moreover, on this community were also assessed the influence of physical and chemical characteristics of water, type of substrate, the environmental integrity of the water body and canopy cover, using multivariate analysis techniques. We sampled low-order sixteen rivers in the dry season, with a collector-type "hand-net" covering the substrates available for benthic fauna. Attributes of community, the wealth of households increased time reforestation. The age of reforestation and environmental integrity of the body of water is presented and correlated between the components assessed, had the greatest influence on the benthic macroinvertebrate community. These results indicated that the benthic macroinvertebrate community requires at least 40 years of reforestation of riparian vegetation to present a structure similar to that present in unaltered environments.